Conversational Repair and Turn-Taking in a Synchronous Online EFL University Classroom - Nisya Rahmaini Marpaung; Sholihatul Hamidah Daulay; Maslathif Dwi Purnomo (Universitas Islam Negeri Palopo, 2026)
This study investigates turn-taking organization and conversational repair in a synchronous online university EFL class at UIN North Sumatra Medan, Indonesia. Applying Conversation Analysis (CA) as its primary analytical framework, the study examines a complete transcript of a recorded online graduate discussion session lasting approximately 28 minutes. The dominant repair type observed is other-initiated other-repair (OIOR), in which the lecturer both identifies the trouble source and provides extended corrective elaboration a repair sequence that spans nearly the entire 26-minute main body of the session. The study demonstrates that the online medium compounds existing institutional asymmetries by removing the proxemic and kinesic cues through which students might ordinarily bid for the floor. Drawing on Schegloff's (2007) CA framework and Walsh's (2011) concept of Classroom Interactional Competence, the paper contributes empirical evidence of how institutional power and technological mediation interact to shape conversation structure in Indonesian higher education EFL contexts. Implications for pedagogy and future research directions are discussed.